Covid-19 and small wineries: new challenges in distribution channel management - Temperini, Valerio; Sabatini, Andrea; Fraboni, Pier Franco Luigi (Piccola Impresa / Small Business, 2022)
Purpose. The present article aims to shed light on the major challenges in distribution channel management that small wineries are called to face after the COVID-19 pandemic. Design/methodology/approach. The study is explorative by adopting a qualitative methodology to analyse the case of a small Italian winery and how it managed distribution activities during COVID-19 pandemic. The study collected data through interviews and secondary data. Results have been abductively developed. Findings. The study delves into the challenges related to managing distribution channels during crises and highlights how the omnichannel approach can support small wineries and help them overcome future crises. Practical and Social implications. The study supports small wineries in understanding how to cope major worldwide crises such as the COVID-19 through the adoption of the omnichannel approach. Originality of the study. The study provides a novel perspective on wine marketing and omnichannel approach management and how the omnichannel approach might be of support to small winery in overcoming crises such as COVID-19. This work contributes to the extant literature on small winery and distribution channel management literature by providing a novel perspective as it empirically investigates the ongoing phenomenon of the COVID-19 crisis.